2007
DOI: 10.1159/000110897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the Expression of mRNA of MMP-7, MMP-9, TIMP-1, TIMP-2 and CEA Tissue Samples from Colorectal Liver Metastases

Abstract: Background: Nowadays we know that survival rates do not differ between repeated and single liver resections for colorectal liver metastases (CLM). To be able to determine patients prone to early recurrence, the use of different markers with a better prognostic value than the routinely employed tumor markers is required. Aim of Study: The aim of our study was to assess mRNA expression of MMP-7, MMP-9, TIMP-1, TIMP-2 and CEA in tissue samples from CLM and their relationship to disease-free interval (DFI) and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…These results are consistent with previous reports that show stroma-restricted expression of the MMPs in human liver metastases of colorectal cancer (21,22). Abundant expression of MMP2 or MMP9 is associated with poor prognosis and high mortality of colon cancer patients (23)(24)(25)(26)(27). Although selective inhibitors of MMP2/9 significantly block mouse liver metastasis of colon cancer and prolong the survival of tumor-bearing mice (28), clinical trials for MMP inhibitors have failed because of severe side effects such as musculoskeletal pain and inflammation (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous reports that show stroma-restricted expression of the MMPs in human liver metastases of colorectal cancer (21,22). Abundant expression of MMP2 or MMP9 is associated with poor prognosis and high mortality of colon cancer patients (23)(24)(25)(26)(27). Although selective inhibitors of MMP2/9 significantly block mouse liver metastasis of colon cancer and prolong the survival of tumor-bearing mice (28), clinical trials for MMP inhibitors have failed because of severe side effects such as musculoskeletal pain and inflammation (29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…Patients having high tissular CEA content in tumors or nonneoplasic mucosa presented a 2-year survival rate of 65.9% (5) . LORENZI et al (25) affirmed that apical expression for tissular CEA presented a significant relationship with degree of differentiation of the neoplasm while diffuse cellular or cytoplasmic expression of this antigen frequently indicates neoplasms extending beyond the intestinal wall and invading lymphatic veins. Studies by NAKAGOE et al (20) analyzing the prognostic value of CEA levels in tumoral tissue, normal colonic mucosa and pre-operative CEA sera in patients with resected colorectal carcinoma, concluded that high CEA levels in neoplasic tissue was the sole independent predictor of adverse evolution following colorectal carcinoma resection.…”
Section: Discussionmentioning
confidence: 99%
“…CEA can also be detected and quantitatively measured in colorectal tumor tissue and normal mucosa (1,2,3,4,5,9,17,12,13,18,26) , but its role in the management of colorectal cancer remains controversial (4,11,20) . Some authors have reported that elevated CEA concentrations within the tumor are correlated with advanced stage (3,4,7,18,22,25,26) , whereas other studies have not reached this conclusion (5,16,20) . In addition, COSIMELLI et al (5) reported that elevated CEA concentrations within colorectal cancer was a predictor for local and distant tumor recurrence after surgery, independent of other recognized prognostic variables (stage and histological grade).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Classical and proliferative tumour markers and matrix metalloproteinases and their tissue inhibitors refl ect the features of malignancy and are useful in prediction of prognosis in patients with colorectal liver metastases (4). There is very limited information about their physiological functions during regeneration and healing of liver parenchyma after any type of liver surgery for malignancy.…”
mentioning
confidence: 99%